The crime of choice: abortion border crossings from Chile to Peru - Freeman, Cordelia (Taylor & Francis, 2017)
Since 1989 abortion in Chile has been illegal in every single circumstance. This means that tens of thousands of women every year undergo clandestine abortions at great risk to their health. Class directly influences Chilean women’s relationships to abortion; wealthier women can pay for the confidentiality of a safe doctor whereas poorer women cannot. There is just one region where women regardless of class can easily travel to another country in search of abortions, Arica in northern Chile. This paper considers the previously unstudied phenomenon whereby women cross the border quickly and cheaply from northern Chile to the Peruvian city of Tacna where numerous clinics offer the procedure. This paper utilises Foucault’s concept of biopolitics to trace how women are forced to cross a border to avoid government legislation and finds that even by leaving the territory of the state, women do not fully leave state control. Despite the lack of official statistics, interviews with healthworkers and a young woman who made the crossing show that abortion border crossings do occur and this paper reflects on the legal, safety, and biopolitical ramifications of these journeys for Chilean women.